Cover Image, Volume 94, Issue 7. Issue 7 (13th June 2019) - Wu, Simiao; Qian, Guangren; He, Zhen
Abstract : The cover image is based on the Research Article Examination of inorganic‐based draw solutes and mitigation of their reverse solute flux in osmotic microbial fuel cells by Simiao Wu et al., DOI:10.1002/jctb.5794 . Abstract : The cover image is based on the Research Article Examination of inorganic‐based draw solutes and mitigation of their reverse solute flux in osmotic microbial fuel cells by Simiao Wu et al., DOI:10.1002/jctb.5794 .